The Oxford handbook of the Brazilian economy - Amann, Edmund; Azzoni, Carlos Roberto; Baer, Werner, 1931-2016 (New York : Oxford University Press, 2018)
Brazil constitutes a globally vital but troubled economy. It accounts for the largest GDP in Latin America and ranks among the world's largest exporters of critical commodities including iron ore, soya, coffee, and beef. In recent years Brazil's global economic importance has been magnified by a surge in both outward and inward foreign direct investment. This has served to further internationalize what has been historically a relatively closed economy. The purpose of this Handbook is to offer real insight into the Brazil's economic development in contemporary context, understanding its most salient characteristics and analyzing its structural features across various dimensions.
Introduction / Edmund Amann, Carlos R. Azzoni -- Brazil's macroeconomic policy institutions quasi-stagnation and the interest rate-exchange rate trap / Luiz Carlos Bresser-Perreira -- Evolution and sectoral competitiveness of the Brazilian manufacturing industry / t Traditional agriculture and land distribution in Brazil / Charles C. Mueller -- Brazil's Agricultural Modernization and EMBRAPA / Geraldo B. Martha Jr., Eliseu Alves -- Manufacturing, services, and the productivity gap / Jorge Arbache -- Growth volatility and economic growth in Brazil / Jorge Arbache, Sarquis J. B. Sarquis -- The Colonial Economy / Flavio Versiani -- Infrastructure / Edmund Amann, Werner Baer, Thomas Trebat, Juan Villa Lora -- Trade policy from the 1930s to the present / t The Economics of Health in Brazil / Antonio Carlos Coelho Campino, Maria Dolores Montoya Diaz, Flavia Mori Sarti -- Brazil, the BRICS, and the changing landscape of global economic governance / Peri da Silva -- Brazilian trade and international economic prospects in an anti-globalization era / Donald V. Coes -- The evolution of Foreign Direct Investment in Brazil / Breno Augusto da Silva e Silva -- Multinational corporations from Brazil / Edmund Amann -- The rise and fall of state enterprises / Armando Castelar Pinheiro -- Antitrust and competition policy in Brazil / Eduardo Pontual Ribeiro, Camila Pires-Alves, Luis Carlos D. Prado -- Corruption scandals, the evolution of anti-corruption institutions, and their impact on Brazil's economy / Mariana Mota Prado, Lindsey Carson -- Energy in Brazil: past and future / t
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 3, 2018).
Keywords: Economic development -- Brazil; Brazil -- Economic conditions; Brazil -- Economic policy